2012
DOI: 10.3354/ab00434
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of Bolinus brandaris (Gastropoda: Muricidae) in the Ria Formosa lagoon (southern Portugal)

Abstract: The purple dye murex Bolinus brandaris is a commercially valuable gastropod in Portugal. However, there is a lack of knowledge on the reproductive cycle in Atlantic populations of this species. In this context, the reproductive cycle of B. brandaris from the Ria Formosa lagoon, southern Portugal, was studied using standard histology and light microscopy and the calculation of bio-physiological indices (gonadosomatic indices for both sexes, penial index for males and capsule gland indices for females). Monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Vasconcelos et al (2008) and Elhasni et al (2010) recommended the use of two indices (GAI and CGI) and considered them simple, practical and efficient for the routine assessment of reproductive activity in a sympatric muricid (H. trunculus). Abidli et al (2012), Vasconcelos et al (2012) and Elhasni et al (2013) confirmed these findings in analogous studies with another sympatric muricid (B. brandaris). Usually, differences in the reproductive cycle are explained by variation in seawater temperature (Lahbib et al 2009, Abidli et al 2012.…”
Section: Discussionsupporting
confidence: 75%
“…Vasconcelos et al (2008) and Elhasni et al (2010) recommended the use of two indices (GAI and CGI) and considered them simple, practical and efficient for the routine assessment of reproductive activity in a sympatric muricid (H. trunculus). Abidli et al (2012), Vasconcelos et al (2012) and Elhasni et al (2013) confirmed these findings in analogous studies with another sympatric muricid (B. brandaris). Usually, differences in the reproductive cycle are explained by variation in seawater temperature (Lahbib et al 2009, Abidli et al 2012.…”
Section: Discussionsupporting
confidence: 75%
“…This could also be applicable on planktonic bivalves encountered in this study but needs further and detailed examination, especially in relation to season and reproductive development around Umm Al-Namil Island and Kuwait coastal waters in general. As for gastropods, the spawning season for Bolinus brandaris (Family: Muricidae) was reported to be between May and July with a clear spawning peak from June to July in Ria Formosa Lagoon in Southern Portugal (Vasconcelos et al, 2012). In this study, Indothais lacera (Family: Muricidae) were observed with eggs on rocks in the intertidal zone of Umm Al-Namil Island on 27 May 2017 (event 9); suggesting spawning period, that could most probably be the start of it, however, this needs further and detailed examination, especially in relation to season and reproductive development for various gastropods to compare in details with the planktonic stages around Umm Al-Namil Island and Kuwait coastal waters in general.…”
Section: The Effect Of Environmental Parameters On Non-ichthyoplanktomentioning
confidence: 99%
“…The reproduction of members of the Muricidae family (at which H. princeps belongs) has been studied in several instances: the gonad cycle of Bolinus brandaris at the South of Portugal (Vasconcelos et al, 2012) and at the South of Tunez (Elhasni et al, 2013). In the Gulf of California, Mexico, Cudney-Bueno et al (2008) carried out observations on the oviposition of the "Black murex" H. nigritus whose findings were similar to those made before by Wolfson (1968) for H. erythrostomus.…”
Section: __________________ Corresponding Editor: Enrique Duprémentioning
confidence: 99%